Can Judicial Institution Stimulate Citizens Well-being in Nigeria? - Tijani, Hakeem Olatunji (African Journal of Stability and Development (AJSD), 2019)
The importance of the judicial institution is informed by its role in bestowing governance that enhances quality of life for Nigerians. Governance as encapsulated in the ability of the state to perform its basic responsibility of providing economic opportunities for its citizens and guaranteeing their security, among others, can be achieved if there is the presence of effective rule of law. This is imperative because the effort of the government in bestowing governance is woven around certain instruments such as policies, strategies and programmes. These instruments are useful determinants of government’s effectiveness on one hand and a denominator for meeting expectations of citizens on the other. These instruments should not infringe on the rights of citizens in any way. To avoid this, the judicial institution should protect them from the juggernaut of government policies. More importantly, citizens have a right to go about their lives in peace in the pursuit of legitimate economic activities, but this is only possible if the institutions of justice and law protect them. In other words, the advancement of citizens is contingent upon an effective judicial institution. Judicial institution strengthens economic growth, reduces poverty and sustains development. This paper, therefore, examines the importance of judicial institution as a bulwark against malgovernace with the duty of improving the quality of life of citizens.